2021
DOI: 10.1038/s41467-021-25464-z
|View full text |Cite
|
Sign up to set email alerts
|

Bicc1 and Dicer regulate left-right patterning through post-transcriptional control of the Nodal inhibitor Dand5

Abstract: Rotating cilia at the vertebrate left-right organizer (LRO) generate an asymmetric leftward flow, which is sensed by cells at the left LRO margin. Ciliary activity of the calcium channel Pkd2 is crucial for flow sensing. How this flow signal is further processed and relayed to the laterality-determining Nodal cascade in the left lateral plate mesoderm (LPM) is largely unknown. We previously showed that flow down-regulates mRNA expression of the Nodal inhibitor Dand5 in left sensory cells. De-repression of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 67 publications
2
30
0
Order By: Relevance
“…Among the validated targets were mRNAs such as cripto1 and dand5 that encode known signaling proteins important for fate decisions in Xenopus and other vertebrate embryos ( Tao et al, 2005 ; Bates et al, 2013 ). Subsequent studies in Xenopus also identified the wnt11b and gdf3 mRNAs as additional authentic Bicc1 targets ( Park et al, 2016 ; Maerker et al, 2021 ). These results defined the Bicc1 target mRNA network and provided a foundation for understanding the molecular events that underlie Bicc1 regulated biological events during vertebrate development and potentially other contexts.…”
Section: Bicaudal-c Target Mrnasmentioning
confidence: 97%
See 1 more Smart Citation
“…Among the validated targets were mRNAs such as cripto1 and dand5 that encode known signaling proteins important for fate decisions in Xenopus and other vertebrate embryos ( Tao et al, 2005 ; Bates et al, 2013 ). Subsequent studies in Xenopus also identified the wnt11b and gdf3 mRNAs as additional authentic Bicc1 targets ( Park et al, 2016 ; Maerker et al, 2021 ). These results defined the Bicc1 target mRNA network and provided a foundation for understanding the molecular events that underlie Bicc1 regulated biological events during vertebrate development and potentially other contexts.…”
Section: Bicaudal-c Target Mrnasmentioning
confidence: 97%
“…Heterotaxy is the abnormal arrangement and structure of the abdominal organs, especially the heart. Recent evidence suggests that L-R defects due to Bicc1 are at least in part due to disrupted Bicc1 regulation of the mRNA encoding the Nodal inhibitor dand5 ( Maerker et al, 2021 ; Minegishi et al, 2021 ). The results from these studies demonstrated the central role of Bicc1 RNA regulation in controlling L-R patterning.…”
Section: Bicaudal-c Regulated Biological Processesmentioning
confidence: 99%
“…Recently, we and others demonstrated that Dand5 reduction is due to the inhibition of dand5 mRNA translation and its subsequent decay. In these studies, the RNA binding protein Bicaudal C1 was identified as the post-transcriptional mediator of flow-induced signaling leading to dand5 mRNA repression ( Maerker et al, 2021 ; Minegishi et al, 2021 ). Upon Dand5 reduction, Nodal is released from sLRO cells and conveys left positional information to the left lateral plate mesoderm (LPM).…”
Section: Introductionmentioning
confidence: 99%
“…BICC1 is a multicellular animal evolutionarily conserved RNA binding protein that plays a vital role in signal transduction pathways, organ development, and homeostasis [ 6 ]. At least three Biccl mutant mice (jcpk, bpk, and 67Gso) have been reported.…”
Section: Introductionmentioning
confidence: 99%